Identifying the Conditions for the Establishment of Venture Capital Funds for Technology Innovation Activities in Vietnam - Minh Thuy, Pham (VNU Journal of Science: Policy and Management Studies; Vol 35 No 4, 2019)
The lack of capital for technology innovation has always been a dilemma for businesses because of the need of large capital for risky technology innovation activities. Venture investment is one of the solutions to capital challenges. Despite being studied since the 90s of the last century, the establishing of venture capital funds and venture investment remains a topical issue in Vietnam. This paper highlights the role of venture capital funds for technology innovation activities as well as the necessary conditions for establishing these funds in Vietnam, such as a perfect market economy, willing venture investors, availability of stock market institutions, etc. On this basis, the paper identifies the insufficient elements for the establishment of venture capital funds in Vietnam.